2021
DOI: 10.3390/nu13093077
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends (1994–2011) and Predictors of Total Alcohol and Alcoholic Beverages Consumption: The EPIC Greece Cohort

Abstract: The aim of this study was to evaluate the longitudinal changes in alcohol consumption (total alcohol and types of alcoholic beverages) of the Greek EPIC cohort participants (28,572) during a 17-year period (1994–2011), with alcohol information being recorded repeatedly over time. Descriptive statistics were used to show crude trends in drinking behavior. Mixed-effects models were used to study the consumption of total alcohol, wine, beer and spirits/other alcoholic beverages in relation to birth cohort, socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(66 reference statements)
1
1
0
Order By: Relevance
“…In regards to the latter, we found that there were more alcohol consumers in low SES irrespective of age, which also had the highest alcohol consumption in agreement with other studies [ 4 , 38 , 39 ]. The International Alcohol Study [ 40 ] demonstrated that drinkers below the poverty line across seven countries had a greater probability of being heavy drinkers, suggesting that the burden of heavier alcohol consumption is falling on people at the most vulnerable end of the socioeconomic spectrum.…”
Section: Discussionsupporting
confidence: 93%
“…In regards to the latter, we found that there were more alcohol consumers in low SES irrespective of age, which also had the highest alcohol consumption in agreement with other studies [ 4 , 38 , 39 ]. The International Alcohol Study [ 40 ] demonstrated that drinkers below the poverty line across seven countries had a greater probability of being heavy drinkers, suggesting that the burden of heavier alcohol consumption is falling on people at the most vulnerable end of the socioeconomic spectrum.…”
Section: Discussionsupporting
confidence: 93%
“…This mediation was suppressive since alcohol intake was higher in individuals with a high SEP, which has also been observed in other studies. [33] , [34] , [35] Of note, the suppressive effect of alcohol was less pronounced in women, which may explain why all associations between the SEP indicators and IHL content were stronger in women. Moreover, the suppressive effect of alcohol was much stronger for the association of low income ( vs. high income) and IHL content, which may explain the non-significant relationship between income and IHL content.…”
Section: Discussionmentioning
confidence: 99%